2017
DOI: 10.1007/s10803-017-3209-y
|View full text |Cite
|
Sign up to set email alerts
|

The Scope and Nature of Reading Comprehension Impairments in School-Aged Children with Higher-Functioning Autism Spectrum Disorder

Abstract: This study of 8-16-year-olds was designed to test the hypothesis that reading comprehension impairments are part of the social communication phenotype for many higher-functioning students with autism spectrum disorder (HFASD). Students with HFASD (n = 81) were compared to those with high attention-deficit/hyperactivity disorder symptomatology (ADHD; n = 39), or typical development (TD; n = 44), on a comprehensive battery of oral language, word recognition, and reading comprehension measures. Results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 113 publications
3
61
1
1
Order By: Relevance
“…Nonword reading requires the child to apply phonological decoding strategies (i.e., utilizing PA and alphabet knowledge), which may explain why PA was a significant predictor in Dynia et al’s [] study. Previous research suggests that some children with ASD may have particular difficulty decoding nonwords [Henderson et al, ; Nation et al, ], whereas other studies have found nonword reading to be intact in school‐age children with ASD, most of whom showed nonverbal cognitive abilities within the typical range [Gabig, ; McIntyre, Solari, Gonzales, et al, ]. Although we measured nonword reading in the current study, significant floor effects were found, with 19 children unable to read any nonwords.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Nonword reading requires the child to apply phonological decoding strategies (i.e., utilizing PA and alphabet knowledge), which may explain why PA was a significant predictor in Dynia et al’s [] study. Previous research suggests that some children with ASD may have particular difficulty decoding nonwords [Henderson et al, ; Nation et al, ], whereas other studies have found nonword reading to be intact in school‐age children with ASD, most of whom showed nonverbal cognitive abilities within the typical range [Gabig, ; McIntyre, Solari, Gonzales, et al, ]. Although we measured nonword reading in the current study, significant floor effects were found, with 19 children unable to read any nonwords.…”
Section: Discussioncontrasting
confidence: 59%
“…More recently, McIntyre, Solari, Grimm, et al [] in their examination of reading profiles of 81 students with high‐functioning ASD (IQ > 75, ages 8–16 years) showed that as a group, performance on three measures of word recognition (nonword reading, sight word reading, and text‐level reading accuracy) was within normal limits (mean standard scores [SSs] 95 and 93 and scaled score of 8, respectively), but variability in performance was high, from severely impaired to above expectations on all measures. In a companion paper, the authors reported that 21% of their sample performed significantly below age expectations in single word reading involving a combination of sight words and nonwords [McIntyre et al, ], and also noted significant difficulties in passage reading accuracy in this group of school‐age students with ASD compared to their peers with attention‐deficit/hyperactivity disorder and their typically developing peers. Taken together, the results from these studies indicate that the group‐level findings that children with ASD show relative strengths on tasks measuring word‐ or passage‐level reading accuracy may mask the significant reading accuracy challenges many individual children with ASD demonstrate.…”
Section: Reading Skills Of Children With Asdmentioning
confidence: 99%
“…8 Assessment of word reading often includes word identification and nonword measures to evaluate the extent to which children apply decoding strategies. Learners with ASD are observed to have average to above average performance on both measures [11][12][13][18][19][20][21] ; however, some studies have shown a portion of these readers scoring better on word recognition than nonword decoding measures, indicating that some learners with ASD may not consistently apply decoding skills. 9,[12][13][14]20,21 Like their peers who struggle to decode, there is some evidence that phonological awareness and syntax predict word recognition skills.…”
Section: Word Recognition and Code-focused Skills And Learners With Amentioning
confidence: 99%
“…Learners with ASD are observed to have average to above average performance on both measures [11][12][13][18][19][20][21] ; however, some studies have shown a portion of these readers scoring better on word recognition than nonword decoding measures, indicating that some learners with ASD may not consistently apply decoding skills. 9,[12][13][14]20,21 Like their peers who struggle to decode, there is some evidence that phonological awareness and syntax predict word recognition skills. 12,[21][22][23] Yet, more research is needed, because there is also evidence that scores of young children with ASD on phonological awareness (i.e., elision and sound blending) measures failed to predict word recognition performance.…”
Section: Word Recognition and Code-focused Skills And Learners With Amentioning
confidence: 99%
See 1 more Smart Citation